Implikasi Pengujian Undang-undang oleh Mahkamah Konstitusi dalam Mewujudkan Maqashid Syari’ah - Lailam, Tanto; Nur Wijayanti, Septi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2018)
This research is about the implications of constitutional review by Constitutional Court in realizing maqashid sharia backgrounded by the ambiguity of whether or not to use the maqashid syariah as a benchmark in constitutional review. The research is to observe the use of maqashid syariah as a benchmark and the implications of the legal system in Indonesia. The method used is normative legal research focusing on several decisions of Constitutional Court. The results of the study show that the Constitutional Court accommodates maqashid sharia. Based on the analysis of Constitutional Court Verdict Number 2-3/ PUU-V/2007, Verdict Number 12/PUU-V/2007, Verdict Number 68/PUU-XII/2014, Verdict Number 85/PUU-XI/2013 show that in constitutional review, the Constitutional Court uses the maqashid syariah as a benchmarks (in the framework ofÂ Pancasila) in line with the idealization of Baldatun Thayyibatun wa Rabbun Ghafur meant to maqashid syariah focusing on maintaining the benefit of religion/din, maintaining the benefit of the soul/nafs, maintaining the benefit of reason/aql, maintaining the benefit of descendants/nasl, and maintaining the benefit of wealth/mal) has been accommodated and applied in constitutional review. The implication is that maqashid sharia becomes one of benchmarks in constitutional review and the Constitutional Court can intepret the contextualization of maqashid sharia in various cases.